Determination the acidity of olive oil samples stored at different periods of times in Tarhouna, Libya - Mahmud Ashtewi S. Ashtewi; Salem Mohammed S. Ahmed (African Journal of Advanced Pure and Applied Sciences, 2025)
Random olive oil samples from local farmers in Tarhouna stored at different periods were investigated to draw a conclusion about their influence with period storage. Ten samples of virgin olive oil stored at different periods (ranged between few months to more than fifteen years) were collected and pre-handled for analysis. The acidity of the samples was determined by volumetric titration using KOH according to the standard BS EN ISO 660 2009. The obtained results showed irregular increase in acidity for samples aged less than three years, while samples aged more than three years showed fairly steady increase in acidity. The study found that the samples stored for more than three years have acidity values exceed codex Alimentarius of olive oil (3.3%), while the samples aged for less than three years have acidity values varied around 3.3%, which may be attributed to poor harvest and pre-extraction procedures, as well as to long storage time.